(untitled) (Revista de Ciências Agroveterinárias, 2004)
Cassava crop (Manihot esculenta Crantz) has been cultivated in all areas of Brazil, especially, in small farmers. However, in Rio Grande do Sul state, the production and planted area were drastically reduced in the last years. This was caused, by low price of the product, which does not stimulate the adoption of new technologies as appropriate agronomic practices and use of superior genotypes. The present work was conducted to evaluate the effect of genotype by enviroment interaction and to estimated the stability and adaptability parameters for root yield of fourteen cassava genotypes in five environments at Rio Grande do Sul state using the Eberhart e Russel (1966) approach. The genotypes were evaluated in four experiments carried out in Vera Cruz - RS and one at Agronomic Experimental Station of UFRGS, in Eldorado do Sul - RS. The results showed that the genotype by environment interaction was highly significant, with root yield in each situation was a function of a combination between each genótipo and a given especific ambient. The greatest oscillation in the cassava root yield was observed in the Aceguá (116%) and S 2 11-35 (114%). On the other hand, the RS 14 genotype showed root yield highest than 24 t.ha-1 in three of the five environments evaluated. The higher frequency of superior root yield, in each genotype, was observed in Vera Cruz in the season station of 2000/01, and in this environment only in the genotype S 75-11 this was not observed. In the experiment conducted in Eldorado do Sul and Vera Cruz in 2002/03, there was a greater concentration of low root yield within the genotypes. The adaptability and stability parameters, in agreement with the Eberhart e Russel approach were achieved in the genotypes Frita, Paraguaia e Apronta a Mesa. In all tested genotypes, just four presented a coefficient of stability equal to zero. This means that most of evaluated genotypes had low root yield previsibility.